The Relationship of Body Mass Index and Waist Circumference with Cardiorespiracy Fitness in Medical Students of UIN Alauddin Makassar - Adellia Tuffahati Dhiya Ulhaq, (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Cardiorespiratory fitness refers to the ability of the heart, lungs, and blood vessels to function optimally, providing adequate oxygen supply to the muscles during physical activity. This research aims to determine the relationship between body mass index and waist circumference with cardiorespiratory fitness in medical students at UIN Alauddin Makassar. The research design is an observational analytic approach with a cross-sectional design. The population in this study consists of all preclinical medical students at UIN Alauddin Makassar. The sampling technique used is purposive sampling, with a minimum sample size of 140. Cardiorespiratory fitness is the dependent variable, while body mass index (BMI) and waist circumference are the independent variables. Data were analyzed using univariate and bivariate tests with SPSS software. The results of the study show a significant relationship between BMI and cardiorespiratory fitness (p-value < 0.05), indicating a moderate negative correlation (r = -0.418). There is also a significant relationship between waist circumference and cardiorespiratory fitness (p-value < 0.05), indicating a strong negative correlation (r = -0.650). This study concludes that there is a significant relationship between BMI and waist circumference with cardiorespiratory fitness in medical students at UIN Alauddin Makassar.